2019
DOI: 10.1111/bjh.16233
|View full text |Cite
|
Sign up to set email alerts
|

Management of anaemia in pre‐term infants

Abstract: Pre-term infants have one of the highest transfusion requirements within the hospital-setting. The vast majority of blood transfusions performed in Neonatal Intensive Care Units (NICUs) are for medically stable pre-term infants with anaemia of prematurity, with the aim of improving oxygen delivery to the vital organs during the crucial phase of growth and development. However, despite the frequency of transfusion in this population, the potential benefits and harms of 'top up' transfusion are not fully underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 100 publications
1
36
2
6
Order By: Relevance
“…Because of differences in size and maturation between fetal sheep and preterm neonates, it is very likely that there are differences in the total size of the EPO-R pool. Compared with the high levels of hematopoiesis in utero, and the expansion of erythroid tissue in the present study after rEPO, preterm neonates have reduced hematopoiesis, leading to physiological anemia in the post-natal period [56].…”
Section: Higher Repo Dose Required In Fetal Sheep Compared To Human Ncontrasting
confidence: 63%
“…Because of differences in size and maturation between fetal sheep and preterm neonates, it is very likely that there are differences in the total size of the EPO-R pool. Compared with the high levels of hematopoiesis in utero, and the expansion of erythroid tissue in the present study after rEPO, preterm neonates have reduced hematopoiesis, leading to physiological anemia in the post-natal period [56].…”
Section: Higher Repo Dose Required In Fetal Sheep Compared To Human Ncontrasting
confidence: 63%
“…Many studies have demonstrated that maternal and reproductive health (e.g., premature birth, LBW, low maternal birth age) are associated with a higher risk of developing childhood anaemia [ 23 , 29 , 30 ]. Consistent with these results, our study showed that these risk factors were strongly associated with higher odds of developing anaemia among Chinese infants aged 0–23 months.…”
Section: Discussionmentioning
confidence: 99%
“…Yine prematüre bebeklerde daha düşük eritrosit ömrü, EPO yetersizliği, eritropoezis için gerekli mikro nutrientlerin (demir, folat, protein, E vitamini ve B12 vitamininin doğumda depolarının düşüklüğü, enteral beslenme yetersizliği veya gastrointestinal sistem immatüritesine bağlı emilim yetersiziliği gibi nedenlerden dolayı) rölatif eksikliği ve prematürenin ko-morbid durumları (kronik akciğer hastalığı, sepsis gibi) prematüre anemisi gelişiminde oldukça önemli etkilere sahiptir. Genel olarak, prematüre anemisi şiddeti düşük gestasyonel yaş ve doğum ağırlığı ile doğru orantılıdır [10].…”
Section: Etiyopatogenezunclassified
“…İyatrojenik kan kaybının mikroteknik içeren laboratuvar yöntemleriyle azaltılması ve non-invazif yöntemlerle hasta yönetiminin (oksijen ve karbondioksit izlemi gibi) sağlanması prematüre bebeklerde anemi gelişimi ve eritrosit transfüzyon ihtiyacını azaltmada oldukça önemlidir [4,10,30]. Aşırı düşük doğum ağırlıklı (<1000 g) 54 bebeğin alındığı bir çalışmada; postnatal ilk 10 haftalık takip süresinde, laboratuvar tetkikleri için kan alımına bağlı kan kayıplarının ilk haftalarda ve gebelik yaşı ile ters orantılı olarak arttığı ve bu süreçte ortalama kan kaybının transfüzyon öncesi yaklaşık 10 ml/kg'ı bulduğu belirtilmektedir [31].…”
Section: Non-farmakolojik öNlemlerunclassified
See 1 more Smart Citation